Active engagement: the legacy of Central America solidarity. - Gosse, Van (NACLA Report on the Americas)
Part of a special section on Pan-American solidarity. The Central America solidarity movement in the U.S. is discussed. Despite its small size—it is unlikely that there were ever more than 20,000 Central America activists at any one time—it was a movement of bewildering diversity with an unusually workable mixture of individual and institutional histories and highly developed organizational practices. This pluralism produced a remarkable enthusiasm and tolerance, as individuals usually went where their instincts and talents led them. It constituted an excellent antidote to the type of sectarianism that had occasionally beset the antiwar movement and earlier solidarity efforts with Latin America. It was a movement that was never concerned with whether or not it could change the U.S. itself, but was instead concerned with changing U.S. policy and offering a meaningful level of material aid on the ground in various countries. Various movement activities are discussed.